The impact of business intelligence through knowledge management. (September 2019) - Bouaoula, Wassila; Belgoum, Farid; Shaikh, Arifusalam; Taleb-Berrouane, Mohammed; Bazan, Carlos
Competition among companies has intensified during the last few decades and hence monitoring the organization's environment has become a priority. Monitoring the internal and external environments involves collecting, retrieving, managing, and disseminating large volumes of data and information. Companies are able to handle these complex tasks very efficiently through knowledge management (KM). A valuable tool of KM is business intelligence (BI), that is, the set of coordinated actions of research, treatment, and distribution of information that can help support the company's competitiveness. This study aims to evaluate BI and quantitatively demonstrate its impact on the competitiveness of an organization. It proposes a methodology and applies it to a multinational food processing company to determine the influencing elements in BI and measure their impacts on the organization's competitiveness. This study identified four variables of BI that are likely to have an impact on the competitiveness of the company: the search for information, the treatment of information, the utility of information, and information security. To collect the required data, this study developed a survey with five categories, namely, research, utility, treatment, security, and competitiveness, and the collected data were analyzed using second-order partial least square-structural equation modeling in SmartPLS 3. This study found that research, utility, treatment, and security have positive correlations with BI, and that the strength of the relationship between BI and each variable is significant. Furthermore, the results show that the BI elements can explain over 38 percent of the variation in the competitiveness of the company.